2020
DOI: 10.1002/adhm.202000735
|View full text |Cite
|
Sign up to set email alerts
|

Silk‐Based Biomaterials for Cardiac Tissue Engineering

Abstract: Cardiovascular diseases are one of the leading causes of death globally. Among various cardiovascular diseases, myocardial infarction is an important one. Compared with conventional treatments, cardiac tissue engineering provides an alternative to repair and regenerate the injured tissue. Among various types of materials used for tissue engineering applications, silk biomaterials have been increasingly utilized due to their biocompatibility, biological functions, and many favorable physical/chemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 190 publications
0
31
0
Order By: Relevance
“…In order to identify 3D printable new materials, suitable for tissue engineering, the ones made of silk proteins are promising candidates [ [26] , [27] , [28] , [29] ]. We have previously demonstrated that materials made of natural silkworm silk and recombinant silk proteins are suitable for cardiac tissue engineering [ [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify 3D printable new materials, suitable for tissue engineering, the ones made of silk proteins are promising candidates [ [26] , [27] , [28] , [29] ]. We have previously demonstrated that materials made of natural silkworm silk and recombinant silk proteins are suitable for cardiac tissue engineering [ [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
“…What is more, new functionalized materials have drawn increasing attention in this field: (1) Besides biocompatibility, the newly-developed materials are expected to offer continuous nutrition supply, facilitating long-term creatures storage under room temperature or in a refrigerator. For example, extracts from silk (sericin and fibroin) are demonstrated to have a variety of biological activities for promoting cellular proliferation and inhibiting apoptosis, and thus benefit tissue regeneration 109 - 111 . Researchers have started to fabricate MNAs using this kind of material for wound recovery, drug delivery, vaccination and so on 112 - 114 .…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…SF has hydrophilic amide groups, hydrophobic areas, and multiple functional groups, giving it the versatility to be conjugated with various filler materials. It has been integrated with gold nanoparticles [ 12 ], graphene(GO) [ 174 ], CNTs [ 175 ], and polystyrene sulphonate (PEDOT: PSS) [ 176 ] for various applications—for example, skin patches for electromyography (EMG) [ 177 ], cardiac mesh electrodes [ 178 ], and textile electrodes for physiological monitoring [ 176 ]. Biocompatible and conductive hydrogels crosslinked with gelatin have led to the development of biomimetic sensors that exhibit the advantages of natural polymers with enhanced physical and electrical properties.…”
Section: Materials Considerations In Wearable Biosensorsmentioning
confidence: 99%